OPTIMIZATION OF CILNIDIPINE NANOSUSPENSION USING A CENTER COMPOSITE DESIGN (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
The purpose of this investigation was to increase the solubility and dissolution rate of Cilnidipine by the preparation of nanosuspensions with solvent antisolvent method at the laboratory scale. Drug solution of Cilnidipine in acetone this mixture was added to stabilizer solution under continuous homogenization. Central composite design was employed to study the effect of the independent variables on the dependent The relationship between the dependent and independent variables was further Elucidated using multiple liner regression analysis (MLRA) and contour plots. Various process and formulation parameters were screened like homogenization speed, solvent to antisolvent ratio, homogenization time, type of stabilizer, concentration of drug and concentration of stabilizer. Physical stability can be enhancing physical stability of this colloidal system; nanosuspensions were freeze dried using D-mannitol. Seven different stabilizers were tried. Among them Poloxamer 407, Poloxamer 188, PVA and Tween 80 yielded nanosuspension in range of 90 to 350 nm. Freeze dried nanosuspensions were filled in capsules to make a deliverable dosage form and almost 100% drug dissolved in 5 minutes. The outcome of this study reveals the immense potential of nanosuspensions for delivery of Cilnidipine by improving its solubility and dissolution rate. These results show that the preparation of Cilnidipine-loaded nanosuspensions significantly improved the in vitro dissolution rate, thus possibly enhancing the fast onset of therapeutic drug effect.